Law and Development of Constitutional Democracy in China: Problem or Paradigm - Peerenboom, Randall (Columbia Journal of Asian Law, 2005)
China is frequently portrayed as a problem case for the law and development movement and modernization theories. For some, the problem is that China has enjoyed remarkable economic growth in the last several decades, apparently without the benefit of “the rule of law,” thus challenging the prevailing view that a legal system that enforces property rights is necessary, if not sufficient for sustained economic growth. For others, the problem is political in nature. China has resisted the third wave of democratization, and remains an officially socialist state, even if a unique twenty-first century version of a socialist state that has endorsed a market economy and rule of law. Some fear that “since China is an increasingly important and influential country in world affairs, China’s continuous anti-democracy diplomacy would have significant impact on the diffusion of . . . democracy throughout the world.” Indeed, some believe that Russia’s recent tilt toward authoritarianism reflects the influence of the success of the Chinese model of markets without democracy.